Ethical Dimensions of Dyadic Communication for Chairs - Rob M McKenzie; Kelly L McKenzie (Academic Chairpersons Conference Proceedings, 2017)
At the center of a Chairpersons responsibilities is their dyadic relations with others. Perhaps more than any other university position, the Chairperson facilitates their duties through one-on-one relationships with students, administrators, staff, and other faculty. These dyadic relationships often create ethical dilemmas because the decisions that must be made in in the context of one dyadic relationship can conflict with another dyadic relationship. This discussion will be facilitated by two presenters: One is a Chairperson of 7 Communication faculty, and the other is an Adjunct Professor in a department of 5 faculty in the Department of Academic Enrichment and Learning. Both presenters will raise various ethical dimensions of dyadic relationships of Chairs, including: advising, registering students for courses, assigning teaching duties, allocating funding, evaluating performance, and selecting channels of communication.
Keywords: Dyadic Communication; Ethical Issues